2014
DOI: 10.5007/1980-0037.2015v17n1p21
|View full text |Cite
|
Sign up to set email alerts
|

Aptidão cardiorrespiratória e nível de atividade física em adolescentes

Abstract: -More objective methods to detect inactive adolescents may help identify young people that are vulnerable to obesity and other chronic diseases. The objective of this study was to examine the association between classifications obtained with the cardiorespiratory fitness test and physical activity level in adolescents, as well as the agreement between tertiles and z-score distribution of the variables generated with these methods (distance covered and total physical activity score). A cross-sectional study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…When overweight/obese children are compared with children with adequate weights, such influence of the CRF does not hold. [6,18,20]. Some authors also suggest that better CRF levels might constrict the hazards of a profile with metabolic risks, as obese and overweight children who have better CRF levels were found to have lower risks in that sense [20,22].…”
Section: R E S U L T Smentioning
confidence: 99%
See 1 more Smart Citation
“…When overweight/obese children are compared with children with adequate weights, such influence of the CRF does not hold. [6,18,20]. Some authors also suggest that better CRF levels might constrict the hazards of a profile with metabolic risks, as obese and overweight children who have better CRF levels were found to have lower risks in that sense [20,22].…”
Section: R E S U L T Smentioning
confidence: 99%
“…Studies show that lower CRF levels are linked with cardiovascular risk and metabolic syndrome [9,15,16]. Some authors suggest that CRF is connected with the nutritional state in children of school age, meaning that good CRF levels are associated with adequate BMI values [17][18][19]. Also, the literature has shown that CRF might influence the relation between obesity and cardiovascular risk [20][21][22].…”
Section: Introductionmentioning
confidence: 99%